RELATION OF POWER-KNOWLEDGE IN BALI MANDARA DISCOURSE - Al Jundi, Fauzan; Ardhana, I Ketut; Suarka, I Nyoman (E-Journal of Cultural Studies; Vol 15 No 2 (2022): Volume 15, Number 2, May 2022DO - 10.24843/cs.2022.v15.i02.p01, 2022)
Bali has great potentials in its beautiful nature and unique culture, which the government uses as an opportunity to implement regional development using the concept of Bali Mandara. This study aims to find out why the development of Bali province applying the concepts of Bali Mandara becomes a polemic for some Balinese, the existence of a power-knowledge relation in the concept of Bali Mandara discourse, and the implications of the development process implementing the Bali Mandara program. The data were analyzed using power-knowledge relation theory and generative structure. The results showed pros and cons in the planning and implementation of the development of the Bali Province. The rules and policies arranged in Regional Regulations (Perda) to support Bali's development are power-knowledge relations that the government applies to achieve the goals. Bali Mandara program has been implemented in less than a decade. Various benefits are the fundamental basis for the readiness of the Balinese to face a better future. Keywords : Bali Mandara, Discourse, Relation, Power-Knowledge.